2020
DOI: 10.5694/mja2.50552
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sales of analgesics to pharmacies after codeine was rescheduled as a prescription only medicine

Abstract: Objective: To investigate changes in sales to pharmacies of over-the-counter (OTC) and prescription analgesics, cold and flu products, and cough suppressants after the rescheduling of codeine as a prescription only medicine in February 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
3
21
1
Order By: Relevance
“…Preliminary data checks suggested comparability of the annual pack numbers and monthly weight fluctuations with previously published IQVIA data [4,14,15]. The monthly series also demonstrated expected seasonal patterns.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Preliminary data checks suggested comparability of the annual pack numbers and monthly weight fluctuations with previously published IQVIA data [4,14,15]. The monthly series also demonstrated expected seasonal patterns.…”
Section: Discussionsupporting
confidence: 52%
“…The purpose of the study was to analyse codeine supply changes associated with up-scheduling in Australia. Previous analyses of pharmaceutical wholesale data found substantial reductions in codeine supply after February 2018 [13][14][15]. Under stable conditions, the wholesale supplies to retail outlets should reflect consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As rates of problematic opioid use and overdose grow in high income countries, epidemiologic signals of exposure and harm have increased year by year. It is therefore encouraging to read evidence of a downward trend for one category of this complex crisis described in two papers in this issue of the Journal …”
mentioning
confidence: 98%
“…The two studies reported in this issue of the Journal provide preliminary indications that rescheduling has not led to the adverse outcomes feared by opponents of upscheduling. Schaffer and her colleagues examined national pharmaceutical sales data before and after rescheduling, and found that the loss of OTC codeine sales was largely offset by increases in those of over‐the‐counter non‐opioid analgesics (paracetamol, ibuprofen, and their combinations), with only a small increase in sales of prescription codeine and none in those of stronger opioids. This finding is consistent with another recent study that found a large decrease in overall codeine use and no marked increase in that of prescription codeine or stronger opioids …”
mentioning
confidence: 99%